Sosialisasi Olahraga Tradisional untuk Meningkatkan Kesehatan Jasmani dan Minat Siswa SD terhadap Pembelajaran Olahraga - Nazirun, Novia; Sari, Merlina (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The physical education learning process can be defined as students' activities in receiving, understanding, and responding to material presented by the teacher. One form of activity rich in educational value is traditional games, which have been proven to contribute to children's intellectual and social development, as well as character formation. However, in the modern era, traditional games are increasingly marginalized and less familiar to students. Yet, traditional games are not only fun but also rich in values of cooperation, tolerance, self-confidence, and can increase learning motivation. This community service activity aims to reintroduce traditional games as a learning medium for Physical Education, Sports, and Health (PJOK) at Muhammadiyah 5 Elementary School in Pekanbaru. Traditional games possess high educational values, such as cooperation, sportsmanship, and physical fitness, but are increasingly marginalized by digital games. The activity methods included outreach, training, and the development of learning modules and video tutorials. The implementation results showed increased student participation and understanding of local cultural values through traditional game activities. This activity is expected to become a sustainable innovation in PJOK learning in elementary schools.